Lokale Antworten auf aufenthaltsrechtliche Prekarität Zugänge zu Gesundheitsversorgung, Unterbringung und Bildung - Ataç, Ilker; Güntner, Simon; Homberger, Adrienne; Kirchhoff, Maren (Gesellschaft und Nachhaltigkeit, 2023)
Migrants with precarious residence status are confronted with restrictions in access to social services in many European countries. With examples from Cardiff, Frankfurt and Vienna, among others, this book describes how municipalities and civil society actors support the affected individuals in the areas of health, housing and education. The contributions highlight the legal, political, and practical challenges of providing for this segment of the local population.